فاعلية استخدام المنظمات الرسومية في تنمية التحصيل وخفض العبء المعرفي المصاحب لحل المشكلات الخوارزمية في الكيمياء التحليلية وأساليب التعلم المفضلة لدى طالبات المرحلة الثانوية بالمملكة العربية السعودية - عزالدين، سحر محمد يوسف (جامعة الإمارات العربية المتحدة - كلية التربية, 2017)
استهدفت الدراسة الحالية بحث فاعلية استخدام المنظمات الرسومية في تنمية التحصيل وخفض العبء المعرفي المصاحب لحل المشكلات الخوارزمية في الكيمياء التحليلية وأساليب التعلم المفضلة لدى طالبات المرحلة الثانوية بالمملكة العربية السعودية، وقد استخدمت الدراسة التصميم شبه التجريبي ذا المجموعتين التجريبية، وشملت (23) طالبة ومجموعة ضابطة وشملت (22) طالبة بالصف الأول الثانوي، وطبقت الدراسة اختبار تحصيلي في الكيمياء التحليلية للصف الأول الثانوي، ومقياس (NASA-TLX) لقياس العبء المعرفي، واختبار حل المشكلات في الكيمياء التحليلية، وقائمة أساليب التعلم المعدلة لكولب ومكارثي، وقد تم استخدام سبعة أنواع من المنظمات الرسومية (خريطة السؤال الكبير، وخريطة السمات، وخريطة تعرف المفهوم، والشكل الهرمي، وخريطة التداخل الدائرية، وخريطة التحليل، وخريطة التدفق)، وتوصلت الدراسة إلى وجود فرق ذو دلالة إحصائية عند مستوى (α=0.05) بين طالبات المجموعة الضابطة والمجموعة التجريبية في الاختبار التحصيلي في الكيمياء التحليلية، ووجود فرق ذو دلالة إحصائية عند مستوى (= a 0.05) بين طلبات المجموعة الضابطة والمجموعة التجريبية في مقياس العبء المعرفي أثناء حل المشكلات الخوارزمية في الكيمياء التحليلية، ووجود فروق دالة إحصائياً في العبء المعرفي المصاحب لحل المشكلات الخوارزمية في الكيمياء التحليلية بين كل من أسلوب التعلم التقاربي وأسلوب التعلم التكيفي لصالح أسلوب التعلم التكيفي، وبين التباعدي والاستيعابي لصالح أسلوب التعلم الاستيعابي، وكذلك أسلوب التعلم التكيفي والتباعدي لصالح أسلوب التعلم التباعدي، كما أنه لا يوجد فرق دال إحصائياً بين العبء المعرفي وأسلوب التعلم التقاربي، وتمت مناقشة النتائج، وتقديم التوصيات والمقترحات المستقبلية.
The present study aimed to examine the impact of using graphic organizers in development of achievement, reduction of cognitive load associated with solving algorithm problems in analytical chemistry and favored learning styles among secondary school students in Saudi Arabia. It has been applied on the female students at secondary first grade, which divided into two groups, experimental group ( 23 students) and a control group (22 students). To verify the impact of the graphic organizers, the study applied achievement test in analytical chemistry, the measure of NASA T-LX to measure cognitive load, problem-solving test in analytical chemistry, and Kolb and McCarthy favored learning styles .The study used seven types of graphic organizers (big question map, features map, flowchart map, Hierarchy Diagram, overlapping circles map, concept definition map and analytical map). The results indicate that there is statistically significant differences at the level (α = 0.05) between the control and experimental group in the achievement test in analytical chemistry, there is statistically significant differences at the level (α = 0.05) between the control and experimental group in cognitive load scale while solving algorithm problems in analytical chemistry, there is statistically significant difference in cognitive load associated with solving algorithm problems in analytical chemistry between each of convergent learning style and adaptive learning style in favor of adaptive learning style , there is statistically significant difference in cognitive load associated with solving algorithm problems in analytical chemistry between divergent and assimilator style in favor of assimilator learning style and there is statistically significant difference in cognitive load associated with solving algorithm problems in analytical chemistry between adaptive and divergent learning style in favor of divergent learning style but there was no statistically significant difference between cognitive load and convergent learning style. The results are discussed and implications of the findings on instructional design application and future research are also presented.
Keywords: التعليم الثانوي -- تدريس العلوم -- طرق التدريس -- الكيمياء التحليلية